Analysis of GDP in Countries allied to Indonesia using a Combination of the GSTAR Model and Verification using Statistical Quality Control - Nur'ainul Miftahul Huda; Nurfitri Imro'ah; Tarisa Umairah; Dewi Setyo Utami; Nani Fitria Arini ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2025)
The Generalized Space-Time Autoregressive (GSTAR) model is used to model GDP growth rates in Indonesia, Malaysia, Singapore, and Brunei Darussalam, allied countries. Southeast Asian countries have cultural and historical linkages and often share economic tendencies. GSTAR is used because it can represent GDP dynamics' complex spatial and temporal relationships. Historical GDP data for the four countries from 1975 to the present is collected. The GSTAR model models regional interdependence and temporal patterns in these economies' geographical and temporal linkages. To test GSTAR model accuracy and robustness, control chart analysis is done. Control charts help monitor and assess economic model stability. The data used in this study is GDP data in Indonesia, Malaysia, Singapore, Brunei Darussalam, and Thailand, was collected from 1975 to 2021. This study discusses GSTAR model projections with actual GDP growth rate data to identify economic abnormalities in these linked countries. This research has major consequences for regional politicians, economists, and businesses. Policy decisions, investment strategies, and GSTAR model economic forecasts can benefit from understanding these countries' GDP growth interdependencies and patterns. Control chart analysis also assures the model accurately tracks economic trends over time. Finally, the GSTAR model and control chart analysis give a complete framework for modeling and testing allied GDP growth rates.